Motif Pembangunan Masjid Cheng Ho Surabaya - Susilo, Suko; Hasanah, Eva Putriya; Syam, Nur (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This article aims to understand in depth the motives for the construction of the Cheng Ho Mosque. This article uses qualitative research methods and data collection techniques, documentation, and direct observation by using a cross-disciplinary research model. There are two motives found, namely the motive of reason and motive of purpose. The motive behind the construction of this mosque is the fear and trauma related to sentiment towards the Chinese ethnic caused by the past experiences of the Chinese ethnic. While on the motive of the goal, the researcher found that the meaning of the goal is that PITI wants to get a lot of support to get a sense of security. The existence of the Cheng Ho mosque has become a significant icon that can introduce the presence of Chinese Muslims.